BIOPOTENSI KELENJAR HIPOFISIS IKAN PATIN (PANGASIUS PANGASIUS) SETELAH PENYIMPANAN KERING SELAMA 0, 1, 2, 3 DAN 4 BULAN - Erma Najmiyati (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Test were conducted to find the biopotency of pituitary glands that havebeen dry-preserved for 0, 1, 2 3 and 4 months. Pituitary glands, obtainedfrom the waste of fillet production plant of Pangasius pangasius, weredried gradually in acetone. The treatments were dry-preservation timespan in dessicator: 0, 1, 2, 3 and 4 months. This hormone biopotencytesting used extract of late-stage of gonad maturation from female andfrom induced-spawning. No significant differences were found in thepercentage of late-stage gonad maturation and ovulation, relativefecundity, fertility and hatchability from every treatment. The number offemales reaching late-stage of gonad maturation were 100% (for allmonths of preservation), while the mean percentages of : relativefecundity was 18.05% (for 3 months of preservation), fertility was 95.73%(for 1 month of preservation), 24-hour hatchability was 31.63% (for 0month of preservation). No significant differences were found for allpreservation time span.